Economic growth and stock market development: Evidence from some selected countries - Dorjdagva, Odbileg; Batchuluun, Jamiyansharav; Damiran, Suvdaa; Natsagdorj, Bayantur (Journal of Eastern European and Central Asian Research (JEECAR), 2024)
By sustaining the required capital and investment, the financial sector plays a critical role in achieving economic growth and stability. This paper conducts a comprehensive examination of the relationships between stock market development and economic growth in 11 post-socialist countries and China. Unbalanced panel data from selected countries from 1995 to 2020 were used for this study. We wanted to disclose the cointegration of crucial variables in assessing Granger causalities using the Vector Auto-Regressive (VAR) model. Our findings confirm the Neutrality Hypothesis (NLH) when we investigated the existence of an independent association between Economic Growth (EG) and the Composite Index of Stock Market Development (SMD). The study’s recommendations emphasize the significance of changing economic policies to account for disparities in economic growth and stock market development to ensure sustainable development in the selected countries.